Blue carbon ecosystems and shark behaviour: an overview of key relationships, network interactions, climate impacts, and future research needs - Dixon, Olivia F. L.; Gallagher, Austin J. (Frontiers in Marine Science, 2023)
Climate change is threatening marine ecosystems and the distribution of species which rely on them. Due to their capacity to sequester vast amounts of carbon, blue carbon ecosystems (BCEs; seagrass, mangroves, salt marshes, kelp forests) are becoming increasingly recognized as key nature-based solutions to climate change. Sharks are mobile species that can exert strong control of food webs and are also key to conservation efforts. BCEs are known to support shark life histories, but the drivers of these relationships remain poorly understood. Here, we highlight two key behavioural pathways directly linking BCEs and sharks (foraging and reproductive activities) and explore the influence of climate on them. Our evaluation of the literature suggested that the physical attributes of the blue carbon plant tissue itself serves as the key link between sharks and BCEs, facilitating high rates of prey biodiversity and a platform for reproductive behaviours. We revealed that shark body size likely has an influence on the nature of these relationships, and that climate may be a modulator of key interactions. We also use basic network theory to explore how ecological information flows throughout BCEs, with sharks as a prominent actor. We identify ways in which future studies can fill knowledge gaps; namely, a focus on smaller endemic species, and empirical assessments between sharks and organic carbon stocks. Maintaining the integrity of these relationships should preserve blue natural capital: BCEs’ capacity to sequester carbon, support local biodiversity, and the role of sharks in preserving resilience.